Kosovo's transformation into a market economy - Novitet Xh. Nezaj (Europa-Kolleg Hamburg, Institute for European Integration, 2015)
This paper explores the development of Kosovo's transformation into a market economy. The first objective is to explore the transition from a centrally planned to an open market economy in Kosovo and to examine the challenges of this transformation over the years. In addition, the paper provides some insights and some quick snapshots of the legislation regarding competition law under the hybrid system of the UN mission and the national institutions of Kosovo. The second objective is to study institutional capacities and the degree of effectiveness of the institutions. Overall, this paper addresses the transition of legislation from the old approach to the new approach, and the beginnings of the Europeanisation of the market economy in Kosovo.
Keywords: 320; transition; market economy; competition rules; privatization; constitution; state capacities